CULTURA GERENCIAL DEL DEPORTE UNIVERSITARIO (Fiep Bulletin - online, 2019)
The purpose of this article is to analyze the vision that social actors have about the managerial culture of universitysports in Ecuador, which involved the selection of key interviewees who have responsibilities in management and/or teaching inhigher education institutions, as well as experience in sports. Based on this premise, the methodology was focused on aqualitative, descriptive, field research and supported by the method of grounded theory in order to conceptually order in opencoding and axial coding the data that were emerging. The results point to a managerial culture that should possess the knowledgeand the desirable competences in the aspirant to direct the university sport and to orient the behavior of the people under hisconduction articulated with the university philosophy. The conclusions derived from this research point to a managerial culturethat in its essence must be sustained - in addition to knowledge - in a firm value system and in an adjusted managerial leadership,conjugated in turn by a set of skills both intra and interpersonal ; in short, a managerial culture that guarantees results turned intobenefits for the university community.